Experimental and Numerical Studies an a Rotating Cavity with Discrete Heat Sources with Conjugate Effects - Jin, L.; Tou, K.; Tso, C. (2005)
An experimental test bed consisting of slip rings and multi-section thermocouples is designed to study periodic rotating heat transfer characteristics from discrete heat sources in an air-filled enclosure, with rotation about its horizontal axis. Physical explanation considering conjugate effects is given, and results are verified by numerical simulations with an in-house program. Results show that there is a steady temperature field in the solid zone and unsteady flow and temperature fields in the fluid zone, for the present set-up, even at low rotation speeds. Effects of rotation to heat transfer in the solid zones are small.